Determine peak hour factor (PHF) based on road type and peak hour time on arterial roads for capacity analysis in East Surabaya - Fatikasari, Aulia Dewi; Alfiansyah, Achmad Dzulfiqar; Rizal, Rikki Sofyan; Wardhani, Primasari Cahya (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2023)
The peak hour factor (PHF) is one of the important factors in planning a road. This factor is used to predict the traffic volume in the planned year of a road. So calculating this factor is very important in planning road capacity so that a road can serve traffic flows well during its design life. The Peak hour factor (PHF) value will vary for each region, each type of road, and each peak hour depending on the traffic flow on that road section. East Surabaya is an industrial and office center area so there are frequent fluctuations in traffic flow at certain hours. This research aims to analyze the Peak hour factor (PHF) value on the arterial road network system in East Surabaya based on road type and peak hour time. The methods used are traffic volume surveys, peak hour volume (PHV) calculations, peak hour factor (PHF) analysis, and residual capacity analysis. The results obtained from this research are that each road section has a different peak hour volume (PHV) time depending on the volume of traffic passing through that road. Apart from that, the type of road and the time peak volume occurs will differentiate the peak hour factor (PHF) value on a road section. Overall, the peak hour factor (PHF) value for arterial roads in East Surabaya with road type 6/2 D is in the range of 0.76-0.97 with an average of 0.91 and road type 4/2 in the range of 0.89 – 0.95 with an average of 0.93.